The Relationship between Parents' Income, Student Gender, School Location, School Resources, and Student Achievement in Middle Schools in Bandung - Desi kristanti; Bhenu Artha (Jurnal Pendidikan West Science, 2023)
This study aimed to investigate the relationship between parents' income, student gender, school location, and student achievement in middle schools in Bandung. A total of 500 middle school students from urban and rural schools in Bandung participated in the study. Results revealed that parents' income and school location were significantly associated with student achievement, while student gender was not. Specifically, students from higher-income families and urban schools had higher achievement scores than those from lower-income families and rural schools. The findings suggest that policymakers, educators, and parents need to pay more attention to addressing the achievement gap between students from different socioeconomic backgrounds and school locations.